Changes in compound hot and dry day and population exposure across China under climate change - Feng, Yao; Sun, Fubao; Liu, Wenbin; Chen, Jie; Wang, Hong; Guo, Qiang; Wang, Yang; Zhang, Qiang; Sang, Yan‐Fang (International Journal of Climatology, 2022)
Hot and dry extremes have co‐occurred with global warming, causing worse threats than single climate extremes. We analyse the compound hot and dry day (CHDD) and population exposure (Epop) across China based on observations and 11 global climate models (GCMs) from the Coupled Model Intercomparison Project Phase 6. The bias‐corrected GCMs, particularly the two‐stage multivariate quantile mapping‐corrected ones, perform better than the raw ones in catching changes in CHDD but they all overestimate CHDD and Epop. More CHDDs occur in the southeast (SE), north (NC) and northwest (NW) China with increasing trends over regions stretching from the northeast (NE) to southwest (SW) China. Despite the declined CHDD, historical Epop has generally increased by the increased population. Future projections in the SSP5‐8.5 experiment indicate an overall increase of CHDD and Epop at 1.5°C warming and an increasing Epop to dangerous CHDD at 2°C warming. SW, NE and the Tibetan Plateau need effective measures of adaptation to reduce sufferings from CHDD under climate change. An average increase of CHDD and population exposure is found in 1.5°C warming relative to the baseline period. SW, NE, NW and TP would experience persistent increasing trends in dangerous CHDD and Epop at 1.5 and 2°C warming levels and are therefore in urgent need of precautionary strategies to reduce sufferings from CHDD under climate change. Changes in frequency of dangerous CHDD and Epop based on the TSQM‐corrected GCMs under 1.5 and 2°C warming scenarios (a2–a3, b2–b3) relative to those (a1, b1) in the baseline period.